2022
DOI: 10.2147/idr.s350976
|View full text |Cite
|
Sign up to set email alerts
|

Ceftazidime/Avibactam versus Polymyxin B in the Challenge of Carbapenem-Resistant Pseudomonas aeruginosa Infection

Abstract: Purpose Ceftazidime/avibactam (CAZ/AVI) monotherapy and polymyxin B-based combination therapy are currently two treatment options for patients with carbapenem-resistant Pseudomonas aeruginosa (CRPA) infection; however, few studies have contrasted the relative efficacy of the two antibiotic regimens. The purpose of this study was to compare the effectiveness of CAZ/AVI and polymyxin B against CRPA infection and analyze the independent predictors of 30-day mortality or sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
(34 reference statements)
1
18
0
Order By: Relevance
“…It was in line with a previous retrospective cohort study of critically ill patients with CRPA infection, which showed a low mortality rate at 14-day (5.9%) and 30-day (13.7%) in the CAZ/AVI treatment group. 21 Besides, Jorgensen et al reported that the 30-day mortality was 17.5% among the patients with CAZ/AVI treatment for MDR-PA infection in their cohort, 22 which was concordant with the data of our study. Consistently, another study evaluating the potential efficacy of CAZ/AVI in MDR and XDR-PA infection, suggested the 30-day mortality were 12.5%, along with clinical cure rate of 50%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was in line with a previous retrospective cohort study of critically ill patients with CRPA infection, which showed a low mortality rate at 14-day (5.9%) and 30-day (13.7%) in the CAZ/AVI treatment group. 21 Besides, Jorgensen et al reported that the 30-day mortality was 17.5% among the patients with CAZ/AVI treatment for MDR-PA infection in their cohort, 22 which was concordant with the data of our study. Consistently, another study evaluating the potential efficacy of CAZ/AVI in MDR and XDR-PA infection, suggested the 30-day mortality were 12.5%, along with clinical cure rate of 50%.…”
Section: Discussionsupporting
confidence: 91%
“…CAZ/AVI is a new β-lactam/β-lactamase inhibitor, which has been approved by FDA for the treatment of complicated urinary tract infections, complicated intra-abdominal infections, hospital-acquired pneumonia, and infections caused by Gram-negative organisms in patients with limited treatment options. 19,20 Available studies had reported the efficacy and safety of CAZ/AVI for refractory P. aeruginosa infection, [21][22][23][24][25] but there is rather limited evidence in lung transplant patients. Thus, the purpose of this study was to investigate the therapeutic efficacy of CAZ/AVI against CRPA infection in lung transplant cases.…”
Section: Introductionmentioning
confidence: 99%
“… 33 , 34 Some studies have shown that the duration of antimicrobial drug use may be a protective factor. 35 In our study, this may be due to the small sample size, but it also reflects the fact that clinical symptoms improve during treatment, allowing for the continued use of antimicrobial drugs until the infection is under control.…”
Section: Discussionmentioning
confidence: 90%
“…The CAZ/AVI group had a significantly higher bacterial clearance rate than the polymyxin B group. 38 Our expert consensus on PA lower respiratory tract infections also states that for CRPA infections, ceftazidime avibactam can be used as a first-line treatment option when sensitivity to it is confirmed by drug sensitivity. 39 The 28-day mortality rate of 64 patients in this study was 37.5%, of which 11 patients died before the return of the drug sensitivity.…”
Section: Discussionmentioning
confidence: 99%